2014
DOI: 10.4149/av_2014_02_120
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in microRNA expression profile in rabies virus-infected mouse neurons

Abstract: Rabies virus (RABV) is known to cause a fatal infection in many mammalian species, yet its pathogenesis remains poorly understood. This study was performed to analyze the microRNA (miRNA) expression profiles in RABV-infected primary neurons of mice. A total of 53 miRNAs were found to be differentially expressed in RABV-infected samples compared with mock samples in a time-dependent manner. Among them, the expression of ten miRNAs was validated by real-time RT-PCR. Potential target genes of differentially expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 31 publications
0
8
1
Order By: Relevance
“…Of the miRNAs with fold change ≥3.0, 5 (miR-155-5p, miR-21-3p, miR-21-5p, miR-223-3p and miR-223-5p) were induced in the brain by both Flury and GX01; 3 (miR-155-5p, miR-223-3p and miR-223-5p) were simultaneously induced in brain and spinal cord by GX01 (Table 2). Our findings on miRNAs differed completely from Zhao and Shi's reports (Zhao et al, 2012a;2012b;Shi et al, 2014), these miRNAs no one the same with Zhao and Shi's findings, suggesting that cause by different virus strain. The data obtained would be very helpful to further explore the relationship between the miRNAs and viral virulence.…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…Of the miRNAs with fold change ≥3.0, 5 (miR-155-5p, miR-21-3p, miR-21-5p, miR-223-3p and miR-223-5p) were induced in the brain by both Flury and GX01; 3 (miR-155-5p, miR-223-3p and miR-223-5p) were simultaneously induced in brain and spinal cord by GX01 (Table 2). Our findings on miRNAs differed completely from Zhao and Shi's reports (Zhao et al, 2012a;2012b;Shi et al, 2014), these miRNAs no one the same with Zhao and Shi's findings, suggesting that cause by different virus strain. The data obtained would be very helpful to further explore the relationship between the miRNAs and viral virulence.…”
Section: Discussioncontrasting
confidence: 97%
“…Functional analysis showed that these differentially expressed miRNAs could be involved in many immune-related signaling pathways, such as Jak-STAT, MAPK, cytokine-cytokine receptor interactions and Fc gamma R-mediated phagocytosis (Zhao et al, 2012a;2012b). In addition, a total of 53 miRNAs were found to be differentially expressed in RABV-infected samples compared with mock samples ( Ghosh et al, 2009;Shi et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, transcriptome profiling revealed the differential expression pattern of long noncoding RNAs (lncRNAs) and miRNAs in RABV infection, and their involvement in multiple immunity-related signal pathways [ 53 , 54 , 55 , 56 , 57 ]. Tu et al reported that miR-455-5p promotes viral replication via the SOCS3/STAT3/IL-6 pathway [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…miR-135a-5p is a negative regulator of STAT3 phosphatase PTPRD and is upregulated in HCV-infected hepatocytes, leading to enhanced STAT3 transcription (49). Some miRNAs, including miR-124, miR-20, and miR-29a, have been reported to be altered in RABV-infected mouse brain and neurons and have been predicted to contribute to immune modulation (34,35,50). These observations led to our hypothesis that the RABV-induced dysregulation of SOCS3/STAT3 was mediated by miRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…Two EBV-encoded genes (LMP1 and EBNA2) are known to promote the expression of miR-155, which is required for the growth of EBV-infected B cells and lymphoma development (33). Several miRNAs, such as miR-124, miR-20, and miR-29a, have been implicated in the RABV infection process by contributing to neuronal dysfunction, while miR-190, miR-203, and miR-145 regulate viral infection-associated JAK-STAT, the T-cell receptor signaling pathway, and natural killer cell-mediated cytotoxicity (34,35). Recent evidence that miR-20a and miR-124 are responsible for neuroremodeling has been obtained (36,37); however, whether the RABV-induced dysregulation of the SOCS3/STAT3 pathway is mediated by miRNAs remains unclear.…”
mentioning
confidence: 99%